The Child Cases: How America's Religious Exemption Laws Harm Children - Rogers, Alan (University of Massachusetts Press, 2013)
Cover -- Title Page -- Copyright -- Dedication -- Contents -- Acknowledgments -- Introduction -- 1. Amy Hermanson -- 2. Shauntay Walker, Seth Glaser, and Natalie Rippberger -- 3. Ian Lundman -- 4. Ashley King -- 5. Robyn Twitchell -- 6. Repeal of Religious Exemptions -- Conclusion: Religious Freedom and the Public Good -- Notes -- Index -- About the Author -- Back Cover